Ett system för mobil administration av egna välgörenhetsinsamlingar - CARLSSON, MICAELA; DAHLGREN, RICHARD (My University, 2017)
Charity organizations have traditionally been collecting funds by collecting money from individuals with donation tins and through advertising. The traditional method has over time transformed into the use of fundraisers on the internet. Star for Life is one of the charity organizations that have begun using the internet to increase their revenue. Individuals can now donate through their website. This solution makes it easier and quicker for the individuals to contribute to fundraisers and thereby increasing Star for Life’s revenue. The implementation of the payment system for donations was created by Sigma IT Consulting. Star for Life has created a strategy to increase the amount of donations from individuals. This strategy aims to provide the ability for individuals to create fundraisers in the organization’s name, where the fundraiser has a specific aim specified by the creator of the fundraiser. The problem in the current version is that the fundraiser creators can’t administer their own fundraisers by, for example, editing the fundraiser’s description or by having the ability to list all donations towards the fundraiser. To solve this problem, Star for Life wants to create a mobile application and through that offer tools to administer the fundraisers. A mobile application makes it possible for individuals who have created a fundraiser to easily administer their own fundraiser on the go. The thesis has resulted in a mobile application for Android that makes it possible for fundraiser creators to administer their fundraisers. Limits of the WordPress REST-API have resulted in a new API being developed alongside the Android application.
Keywords: Informations- och kommunikationsteknik; Data- och informationsvetenskap; Information & Communication Technology; Computer and Information Science